Workshop processes, practices and materials - Black, Bruce J.; ebrary, Inc. (Burlington, MA : Newnes/Elsevier, 2010)
Workshop Processes, Practices and Materials is an ideal introduction to workshop processes, practices and materials for entry-level engineers and workshop technicians. With detailed illustrations throughout and simple, clear language, this is a practical introduction to what can be a very complex subject. It has been significantly updated and revised to include new material on adhesives, protective coatings, plastics and current Health and Safety legislation. It covers all the standard topics, including safe practices, measuring equipment, hand and machine tools, materials and joining methods, making it an indispensable handbook for use both in class and the workshop. Its broad coverage makes it a useful reference book for many different courses worldwide.
Workshop Processes, Practices and Materialsis an ideal introduction to workshop processes, practices and materials for entry level engineers and workshop technicians. With detailed illustrations throughout, and simple, clear language, this is a practical, one book introduction to what can be a very complex subject. It has been significantly updated and revised to include new material on adhesives, protective coatings, plastics and current Health and Safety legislation. It covers all the standard topics including safe practices, measuring equipment, hand and machine tools, materials and joining methods, making it an indispensable handbook for use both in class and the workshop. Its broad coverage makes it a useful reference book for many different courses worldwide, including BTEC First Engineering and other NVQ Level 2 engineering courses from City and Guilds. A practical workshop text, with the essential information on workshop practice needed by students new to the field of mechanical engineering End of chapter review questions help reinforce chapter content Clear, straightforward writing style, with detailed illustrations throughout, to improve accessibility for visual learners
Safe practices; Hand processes; Marking out; Sheet-metal operations; Measuring equipment; Cutting tools and cutting fluids; Drilling; Shaping; Turning; Surface grinding; Milling; Joining methods; Moving loads; Drawing, specifications and data; Materials; Plastics; Primary forming processes; Presswork; Investment casting and shell moulding; Die-casting.
Title from digital title page (viewed on Apr. 21, 2011)
Keywords: Machine-shop practice